PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT RSUD - Asmuruf, Morinda Cetrifolia Sirmonia; Sudarwadi, Dirarini; Tata, Jan Felarius (Cakrawala Management Business Journal, 2025)
This study aims to determine and analyze the influence of job satisfaction and job stress on nurse performance in the inpatient ward of the Regional General Hospital. The research used a quantitative approach with an associative method using saturated sampling of 62 inpatient ward nurses. Data collection techniques used questionnaires that had been tested for validity and reliability. Data analysis used multiple linear regression with t-test, F-test, and coefficient of determination. The results show that partially, job satisfaction has no significant effect on nurse performance (t-count = 0.855 < t-table = 2.001; sig. 0.396 > 0.025), while job stress has a negative and significant effect on nurse performance (t-count = 9.648 > t-table = 2.001; sig. 0.000 < 0.025). Simultaneously, job satisfaction and job stress have a significant effect on nurse performance (F- count = 46.717 > F-table = 4.00; sig. 0.000 < 0.05) with an R² value of 0.613 or 61.3%. These results indicate that good job stress management is a crucial factor in improving nurse performance in the inpatient ward of RSUD.